Gender Effects, Culture and Social Influence in the Dictator Game: An Italian Study - Niall O'Higgins; Arturo Palomba; Patrizia Sbriglia (Institute for the Study of Labor (IZA), 2015)
There is little consensus on whether women are more generous than men; some research results indicate a higher propensity towards giving of female dictators, whilst others suggest the opposite. Two explanations have been put forward. According to the first one, women are more generous than men and the conflicting results are due to the way preferences are elicited (Eckel and Grossman, 2002), since women are more sensitive to "social cues" and their preferences are more "malleable" (Croson and Gneezy, 2009). According to the second one, the institutional culture and the role women have in society are key elements in shaping gender differences in preferences. In fact, in matrilineal societies (Gong et al.; 2014; Gneezy et al.; 2009), women are self-oriented, more competitive and less generous than men, since they have an important role as economic decision makers in the family and the society. We test these alternative hypotheses running Dictators experiments in Italy, a western country with a matrilineal culture, introducing at the same time - social influence in the design. We find more support to the hypothesis on the cultural role in shaping preferences, rather than the effects of social influence.
Keywords: C90; C91; D03; J16; 330; social influence; gender; social preferences; experiments; dictator game